An anthracene heterocyclic thioacrylate compound, a preparation method and application thereof

CN122726043BActive Publication Date: 2026-10-27JIANGSU SHIKE NEW MATERIAL CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202611185896.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2026-08-06
Publication Date
2026-10-27
Estimated Expiration
2046-08-06

AI Technical Summary

Technical Problem

现有蒽环改性丙烯酸酯产品存在明显结构性缺陷:多为直接刚性接枝蒽环结构,分子链无柔性过渡基团,导致改性单体与树脂基体组分相容性差,固化过程中应力分布不均,存在固化收缩率偏高、光学均匀度差、成品雾度超标等问题,最终造成光学镜片成像畸变、清晰度下降,严重影响光学使用效果

Benefits of technology

(1)蒽杂环稠芳环侧基(C14H9)结构提高光学树脂材料折射率和耐候性。蒽杂环稠芳环侧基(C14H9)结构具有极高的分子电子云密度,可显著提升单体及固化后树脂的整体折射率,满足高折射率光学基材需求,适配高端轻薄光学产品设计;同时,蒽杂环具备优异的紫外吸收能力和光热稳定特性,可从分子层面赋予光学树脂基材优异的抗紫外阻隔能力,解决传统光学树脂长期光照黄变、透光率衰减的问题,提升镜片耐候性。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122726043B_ABST
    Figure CN122726043B_ABST
Patent Text Reader

Abstract

An anthracene heterocyclic thioacrylate compound, a preparation method and application thereof, the compound has a structure as shown in general formula (A), the acrylate compound molecular structure contains anthracene heterocyclic functional groups, thioether flexible bridge, methyl methacrylate active end group, the technical defects of traditional thioacrylate optical resin are systematically solved from the molecular structure level, and the application requirements of different optical material raw materials are adapted; the application also provides an efficient preparation process of the compound, which has excellent optical properties such as high refractive index and low dispersion, and can significantly improve the yellowing resistance of acrylic optical material. (A).
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of organic polymer optical materials technology, specifically relating to an anthracene heterocyclic thioacrylate compound and its preparation method. Background Technology

[0002] Optical resins are one of the core substrates for optical lenses and precision optical components. Among them, thioacrylate resins, due to their high refractive index caused by sulfur atoms, are the mainstream research direction for high-end optical substrates. However, conventional thioacrylate optical resins have many inherent technical shortcomings, making it difficult to meet the requirements for manufacturing high-end lenses that are ultra-thin, highly transparent, have low dispersion, and are resistant to aging.

[0003] Conventional thioacrylates have a simple molecular structure design, relying solely on monosulfide groups to increase the refractive index without the support of functional stabilizing groups. This results in significant defects in the overall optical and weather resistance properties of the material: First, the substrate has poor photostability, and under long-term exposure to ultraviolet and visible light, molecular chains are prone to aging and breakage, leading to resin yellowing, a continuous decrease in light transmittance, and a significant reduction in the lifespan of optical lenses. Second, the UV protection capability is weak, failing to effectively block environmental ultraviolet radiation, making it difficult for lenses to meet the requirements of daily eye care and UV protection for precision optical equipment. Third, the overall molecular structure lacks rigidity and dispersion control, making it impossible to simultaneously achieve high refractive index and low dispersion performance, resulting in chromatic aberration and distortion in imaging, and making it difficult to adapt the imaging accuracy to high-end optical scenarios. At the same time, traditional thioacrylates have poor structural regularity after curing, lack optical control functions, and have insufficient functional expansion capabilities.

[0004] Anthracene heterocyclic fused aromatic ring systems possess unique advantages such as high electron cloud density, excellent UV absorption performance, and good photothermal stability. They also exhibit special photoreversible optical response characteristics, making them ideal functional groups for improving the refractive index, UV resistance, and yellowing resistance of optical resins. Currently, most anthracene-modified optical resins in the industry focus on ordinary acrylate systems, with research on anthracene heterocyclic directional modification technology for sulfide-bridged methacrylates almost nonexistent. Existing anthracene-modified acrylate products suffer from significant structural defects: they are mostly directly rigidly grafted anthracene ring structures, lacking flexible transition groups in the molecular chain. This leads to poor compatibility between the modified monomer and the resin matrix components, uneven stress distribution during curing, high curing shrinkage, poor optical uniformity, and excessive haze in the finished product, ultimately causing imaging distortion and reduced clarity in optical lenses, severely impacting optical performance. Furthermore, existing modified products involve complex preparation processes, high reaction energy consumption, and difficult product purification, resulting in high production costs and hindering large-scale mass production applications of high-end optical substrates.

[0005] Addressing the current market's urgent need for high-refractive-index, low-dispersion, low-yellowing, high-transmittance, and highly weather-resistant high-end optical resin monomers, this research solves the industry pain points of traditional products, such as the inability to simultaneously achieve both refractive index and dispersion, poor aging resistance, and unsatisfactory molding quality. It has significant engineering application value and market prospects for the preparation of high-quality eye-protecting optical lenses and high-end functional optical components. Summary of the Invention

[0006] To address the aforementioned problems in the prior art, this invention provides an anthracene heterocyclic thioacrylate compound, its preparation method, and its applications. The compound structure is shown in Formula A. This invention systematically solves the technical defects of traditional thioacrylate optical resins at the molecular structure level through the precise combination design of anthracene heterocyclic functional groups, thioether flexible bridging bonds, and methacrylate active end groups. The modified optical resin prepared from this compound possesses multiple core advantages such as high refractive index, low dispersion, resistance to yellowing, high stability, and ease of processing, significantly improving the optical and mechanical properties of the material and meeting the application requirements of high-end optical materials.

[0007] To achieve the above objectives, the present invention provides the following technical solutions: On the one hand, the present invention provides an anthracene heterocyclic thioacrylate compound, the structure of which is shown in formula (A):

[0008] (A).

[0009] On the other hand, the present invention provides a method for preparing compound A as described above, the method comprising the following steps: Step 1: Using 9-anthracene ethyl thiols and chloroethanol as raw materials, a thioetherification reaction is carried out under the action of a catalyst (acid-base solution) to generate 2-([2-(9-anthracene)ethyl]thioethanol) (Formula I).

[0010] C 14 H9-CH2CH2-SH + ClCH2CH2OH →C 14 H9-CH2CH2-S-CH2CH2OH + HCl

[0011] (I) Step 2: The above-mentioned 2-([2-(9-anthrayl)ethyl]thio)ethanol and methacryloyl chloride are subjected to an esterification reaction in an alkaline environment to generate 2-[(anthrayl-9-ylethyl)thio]ethyl methacrylate.

[0012] C 14H9-CH2CH2-S-CH2CH2OH + CH2=C(CH3)COCl →CH2=C(CH3)COO-CH2CH2-S-CH2CH2-C 14 H9+ HCl

[0013] (A) Specifically, the method includes the following steps: I. Thioetherification reaction: Dissolve 9-anthracene ethyl mercaptan in an anhydrous solvent, cool to -3~0℃ in an ice bath, and purge with N2 throughout the process; add acid-base solution dropwise and stir for 10~20 min, then add 2-chloroethanol dropwise for 90~120 min, and raise the temperature to room temperature for 3~6 h. The molar ratio of 9-anthracene ethyl mercaptan, acid-base solution and 2-chloroethanol is 1:(1.2~2.5):(1.5~3.5); filter to remove salt, and rotary evaporate to remove solvent, to obtain a yellow oily 2-([2-(9-anthracene)ethyl]thio)ethanol intermediate.

[0014] II. Esterification reaction: Add polymerization inhibitor, 2-([2-(9-anthrayl)ethyl]thioethanol, and acid-base solution to a reaction vessel containing solvent. Probe with N2 throughout the reaction. Cool to -3 to 0°C in an ice bath. Stir until completely dissolved. Slowly add methacryloyl chloride, maintaining a temperature <5°C. After addition, raise the temperature to room temperature and react for 1.5 to 2.5 hours. The molar ratio of 2-([2-(9-anthrayl)ethyl]thioethanol, acid-base solution, and methacryloyl chloride is 1:(1.2~3):(1.5~3.5). After the reaction, raise the temperature to room temperature. Wash the organic phase with deionized water, saturated sodium bicarbonate solution, and saturated brine until neutral. Dry with anhydrous sodium sulfate, filter, and remove the solvent from the filtrate by vacuum distillation. The crude product is purified by column chromatography with a petroleum ether-ethyl acetate volume ratio of (7~3):1, yielding compound A, 2-[(anthrayl-9-ylethyl)thio]ethyl methacrylate.

[0015] In the preparation method described above, preferably, the solvent in step I is selected from at least one of diethyl ether, tetrahydrofuran, dichloromethane, cyclopentyl methyl ether, dimethyl sulfoxide, and isopropyl acetate.

[0016] In the preparation method described above, preferably, the molar ratio of 9-anthracene ethyl thiol to solvent is 1:(3~9).

[0017] In the preparation method described above, preferably, the solvent in step II is selected from at least one of dimethyl sulfoxide, N,N-dimethylacetamide, and N,N-dimethylformamide.

[0018] In the preparation method described above, preferably, the molar ratio of 2-([2-(9-anthrayl)ethyl]thio)ethanol to solvent is 1:(3~9).

[0019] In the preparation method described above, preferably, the acid-base solution in steps I and II is selected from at least one of dimethylamine, diethylamine, triethylamine, potassium carbonate, sodium carbonate, sodium hydroxide, potassium hydroxide, and 4-dimethylaminopyridine.

[0020] In the preparation method described above, preferably, the polymerization inhibitor in step II is at least one of hydroquinone, hydroquinone monomethyl ether, and 2,6-di-tert-butyl-p-cresol.

[0021] In the preparation method described above, preferably, the molar amount of the polymerization inhibitor is 1 to 3% of the molar amount of 2-([2-(9-anthrayl)ethyl]thioethanol).

[0022] The application of anthracene heterocyclic thioacrylate compounds as described above in the preparation of modified acrylic optical resin materials.

[0023] In another aspect, the present invention provides the application of the anthracene heterocyclic thioacrylate compound of formula A in the preparation of modified acrylic optical resin optical materials.

[0024] The beneficial effects of this invention are reflected in the following aspects: (1) Anthracene heterocyclic fused aromatic ring side group (C 14 The H9 structure improves the refractive index and weather resistance of optical resin materials. Anthracene heterocyclic fused aromatic ring side groups (C...) 14 The H9 structure has an extremely high molecular electron cloud density, which can significantly improve the overall refractive index of the monomer and the cured resin, meeting the requirements of high refractive index optical substrates and adapting to the design of high-end thin and light optical products. At the same time, the anthracene heterocycle has excellent ultraviolet absorption capacity and photothermal stability characteristics, which can endow the optical resin substrate with excellent anti-ultraviolet blocking ability at the molecular level, solving the problems of yellowing and light transmittance decay of traditional optical resins after long-term light exposure, and improving the weather resistance of lenses.

[0025] (2) The flexible sulfide bridging bond (-CH2-S-CH2CH2-) can improve the imaging accuracy and mechanical properties of optical resin materials. Introducing a flexible sulfur atom bridging structure between the ester group and the anthracene heterocyclic ring, unlike the traditional rigid anthracene ring grafting structure, allows the flexible transition of the sulfide bond to effectively optimize the internal stress distribution of the molecule, reduce optical dispersion, eliminate chromatic aberration and distortion problems in lens imaging, and significantly improve optical imaging accuracy. Simultaneously, the flexible sulfide bridging bond can improve the molecular chain toughness of the cured resin, improving the brittleness and cracking defects of traditional high-rigidity optical lenses, and enhancing the impact resistance and safety of finished optical products.

[0026] (3) Methacrylate end group (CH2=C(CH3)-COO-) has a moderate polymerization temperature during the curing process, which can achieve uniform cross-linking of the resin system. The curing cross-linking density is stable and controllable, which effectively solves the problems of large curing shrinkage, poor optical uniformity and excessive haze of traditional modified resins. It is compatible with both light and heat curing lens mass production processes and has strong process compatibility.

[0027] (4) The integrated molecular covalent grafting structure of anthracene heterocyclic-thioether bridge-methacrylate has stable bonding of each structural unit, which completely solves the problems of poor component compatibility, easy layering and unstable performance in traditional physical modification and simple grafting modification. The compound has high purity and good storage stability.

[0028] (5) The preparation process of the compound of the present invention is simple, the reaction is highly controllable, and the product purification is easy, which greatly reduces production energy consumption and production cost, and has broad industrialization prospects. Attached Figure Description

[0029] Figure 1 The FT-IR infrared spectrum of the 2-[(anthracene-9-ylethyl)thio]ethyl methacrylate compound prepared in Example 1.

[0030] Figure 2 The 1H NMR spectrum of the 2-[(anthracene-9-ylethyl)thio]ethyl methacrylate compound prepared in Example 1.

[0031] Figure 3 The FT-IR infrared spectrum of the 9-anthracene ethyl thiol compound prepared in Example 1 is shown.

[0032] Figure 4 The 1H NMR spectrum of the 9-anthracene ethyl thiol compound prepared in Example 1 is shown.

[0033] Figure 5 The FT-IR infrared spectrum of the 2-([2-(9-anthrayl)ethyl]thioethanol compound prepared in Example 1 is shown.

[0034] Figure 6 The 1H NMR spectrum of the 2-([2-(9-anthrayl)ethyl]thioethanol compound prepared in Example 1. Detailed Implementation

[0035] The present invention will be further described below through specific embodiments, but this does not imply a limitation on the scope of protection of the present invention.

[0036] Example 1 Preparation of 2-[(anthracene-9-ylethyl)thio]ethyl methacrylate (Formula A) (1) Preparation of 9-anthracene ethyl mercaptan In a reaction vessel equipped with a condenser, stirrer, and nitrogen delivery tube, 250 g of 2-(9-anthrayl)bromoethane and 73.5 g of thiourea were added, along with 3250 mL of anhydrous ethanol. The mixture was stirred until fully dissolved. Under continuous N2 protection, the mixture was heated to 76 °C and refluxed for 6 h, during which solid isothiourea hydrobromide precipitated. The system was kept under stable reflux. 265 g of 40% sodium hydroxide solution was added dropwise over 90 min, and reflux was continued for 2.5 h for hydrolysis. Heating was stopped, and the mixture was allowed to cool naturally to room temperature. The mixture was then cooled in an ice-water bath, and dilute hydrochloric acid was slowly added dropwise with stirring to acidify the pH to 3, resulting in a large amount of crude solid product. Dichloromethane (3 × 600 mL) was added for extraction. The organic phases were combined, washed three times with saturated brine, dried over anhydrous sodium sulfate, filtered to remove the desiccant, and the solvent was removed by rotary evaporation under reduced pressure to obtain 157.4 g of 9-anthraethylthiol.

[0037] The obtained compounds were subjected to Fourier transform infrared spectroscopy (FT-IR) and 1H NMR nuclear magnetic resonance spectroscopy.

[0038] Infrared spectroscopy FT-IR testing, such as Figure 3 As shown, its infrared characteristic peak (wavenumber cm⁻¹) -1 Peak attribution): 3060~3030cm -1 The multiplets represent the CH stretching vibrations of anthracene and aromatic rings; 2930 cm⁻¹ -1 2862 cm -1 The double peaks represent the asymmetric and symmetric CH stretching vibrations of the methylene group; 2575–2550 cm⁻¹ -1 The sharp peak is a characteristic peak of the SH stretching vibration and thiol group; 1620–1465 cm⁻¹ -1 Multiple sets of multiple peaks indicate the stretching vibration of the anthracene fused-ring aromatic C=C skeleton; 1462 cm⁻¹ -1 The medium-intensity peak is due to the methylene shear bending vibration; 1378 cm⁻¹ -1 The weak peak is due to the in-plane bending vibration of alkyl CH4; 900–650 cm⁻¹ -1 The strong multiple peaks are in the anthracene ring fingerprint region, with peaks at 872–860 cm⁻¹. -1 Characteristic peaks for 9-substituted anthracene; 780–735 cm⁻¹ -1 It is absorbed by the overall out-of-plane vibration of the anthracene ring fused ring.

[0039] Nuclear magnetic resonance hydrogen spectrum such as Figure 4As shown: δ8.36 (s, 1H): anthracene ring H10 (characteristic singlet of anthracene with 9-position substitution); 8.00–7.90 (m, 4H): anthracene ring α-aryl hydrogen (H1, H4, H5, H8); 7.50–7.38 (m, 4H): anthracene ring β-aryl hydrogen (H2, H3, H6, H7); 3.12 (t, 2H): methylene group directly attached to the anthracene ring (An-CH2); 2.72 (dt, 2H): methylene group near the thiol group (-CH2-SH); 1.62 (t, 1H): broad peak is thiol intermolecular hydrogen (-SH).

[0040] (2) Preparation of 2-([2-(9-anthrayl)ethyl]thioethanol 1800g of 9-anthracene ethyl mercaptan was dissolved in 3600g of anhydrous tetrahydrofuran, cooled to 0°C in an ice bath, and protected with N2. 1200g of triethylamine was added dropwise and stirred for 15 min. 1450g of 2-chloroethanol was added dropwise over 100 min, and the mixture was allowed to rise to room temperature for 4.5 h. The mixture was filtered to remove salts and rotary evaporated to remove solvents, yielding 1802.3g of a yellow oily 2-([2-(9-anthracene)ethyl]thio)ethanol intermediate.

[0041] The obtained compounds were subjected to Fourier transform infrared spectroscopy (FT-IR) and 1H NMR nuclear magnetic resonance spectroscopy.

[0042] Infrared spectroscopy FT-IR testing, such as Figure 5 As shown, its infrared characteristic peak (wavenumber cm⁻¹) -1 Peak assignments: The strong absorption peak at 3420–3305°C indicates the OH stretching vibration, suggesting the presence of terminal hydroxyl groups; the absorption peak at 3060–3032°C indicates the CH stretching vibration of the aromatic ring in anthracene ring; the doublet at 2930°C and 2860°C indicates the CH stretching of saturated methylene groups, suggesting the complete disappearance of thiol groups; the multiplet at 1622–1470°C indicates the stretching vibration of the aromatic C=C skeleton of the anthracene ring; the absorption peak at 1460°C indicates the methylene bending vibration; the absorption peak at 1380°C indicates the CH bending vibration; the strong absorption peak at 1060–1045°C indicates the CO stretching vibration; the absorption peak at 903–650°C indicates the out-of-plane bending of the aromatic ring CH; the absorption peak at 880–865°C is a characteristic peak of 9-substituted anthracene; and the multiplet at 780–740°C is the overall fingerprint of the fused anthracene ring. Among these, the aliphatic sulfide CS stretching vibration absorption intensity is extremely low and is located in the 650–780°C fingerprint region, covered by the multiplet of the out-of-plane bending vibration of the aromatic hydrogens of the anthracene ring, making it impossible to observe any independent characteristic absorption peaks.

[0043] Nuclear magnetic resonance hydrogen spectrum such as Figure 6As shown: the characteristic singlet at δ 8.38 (s, 1H) is that of 9-substituted anthracene, belonging to anthracene H-10; the multiplets at 8.02–7.92 (m, 4H) are the α-aryl hydrogens on both sides of the anthracene ring; the multiplets at 7.52–7.40 (m, 4H) are the β-aryl hydrogens of the anthracene ring; 3.68 (t, 2H) is the methylene group (-CH2-OH) on the oxygen side of the hydroxyethyl group; 3.02 (t, 2H) is the methylene group (9-An-CH2) adjacent to the anthracene ring of the anthracene ethyl group; the two overlapping triplets at 2.78–2.66 (m, 4H) are the methylene group (-CH2-S-CH2) adjacent to the sulfur atom; and the broad singlet at 2.30 (br s, 1H) is the active hydrogen of the hydroxyl group (-OH).

[0044] (3) Preparation of 2-[(anthracene-9-ylethyl)thio]ethyl methacrylate (formula A) 1800 g of the prepared 2-([2-(9-anthrayl)ethyl]thio)ethanol was stirred and added to a reaction vessel containing 3450 g of dichloromethane. Under N2 protection, 25 g of 2,6-di-tert-butyl-p-cresol and 1200 g of triethylamine were added with stirring. After complete dissolution, 1350 g of methacryloyl chloride was added dropwise over 60 min. The temperature was maintained at 2°C, and after the addition was complete, the mixture was allowed to rise to room temperature for 2 h. The organic phase was washed with deionized water, saturated sodium bicarbonate solution, and saturated brine, dried over anhydrous sodium sulfate, filtered, and the filtrate was subjected to vacuum distillation to remove the solvent. The crude product was purified by column chromatography (petroleum ether-ethyl acetate volume ratio = 6:1) to obtain 1769.4 g of 2-[(anthrayl-9-ylethyl)thio]ethyl methacrylate. Yield: 78.3%.

[0045] 2-[(anthracene-9-ylethyl)thio]ethyl methacrylate was subjected to Fourier transform infrared spectroscopy (FT-IR) and 1H NMR nuclear magnetic resonance spectroscopy.

[0046] FT-IR infrared spectroscopy: such as Figure 1 As shown in the figure, the curve analysis shows that the range is 3080~3010cm. -1 The absorption peak at 2850–2995 cm⁻¹ corresponds to the stretching vibration of the anthracene ring (CH). -1 The absorption peak at 1720-1735 cm⁻¹ corresponds to the stretching vibration of aliphatic CH groups. -1 The strong absorption peak is a characteristic peak of the C=O stretching vibration of the ester carbonyl group, 1630~1640 cm⁻¹. -1 The absorption peak at 1505–1515 cm⁻¹ corresponds to the C=C stretching vibration of the carbon-carbon double bond. -1 The absorption peak at 1470–1450 cm⁻¹ corresponds to anthracene ring skeletal vibrations. -1 The absorption peaks at 1370–1380 cm⁻¹ correspond to the CH bending vibrations of the methyl and methylene groups, respectively. -1The absorption peak at 1150-1300 cm⁻¹ is a characteristic peak of methacrylate. -1 The multiple absorption peaks at 710–900 cm⁻¹ correspond to the COC stretching vibration of the ester bond. -1 The absorption peak at 645 cm⁻¹ is due to the out-of-plane bending vibrations of vinyl=CH₂ and anthracene ring aryl hydrogens; -1 The absorption peak at this point is a characteristic peak of the stretching vibration of the CS thioether bond.

[0047] The results of the 1H NMR spectroscopy analysis are as follows: Figure 2 As shown, curve analysis reveals that δ = 7.33~8.50 ppm (m, 9H, anthracene aromatic hydrogen C). 14 H9), 5.50~6.22 ppm (dd, 2H, ethylene terminal hydrogen =CH2), 3.05~4.40 ppm (tt, 4H, methylene hydrogen CH2CH2-S-), 2.60~2.85 ppm (m, 4H, -S -CH2CH2 methylene hydrogen), 1.80~1.95 ppm (s, 3H, CH2=C-CH3 methyl hydrogen).

[0048] Example 2 Preparation of 2-[(anthracene-9-ylethyl)thio]ethyl methacrylate (Formula A) 1350g of 9-anthracene ethyl mercaptan was dissolved in 2650g of anhydrous tetrahydrofuran, cooled to 0°C in an ice bath, and protected with N2. 900g of triethylamine was added dropwise and stirred for 15 min. 1000g of 2-chloroethanol was added dropwise over 100 min, and the mixture was allowed to rise to room temperature for 4.5 h. The mixture was filtered to remove salts and rotary evaporated to remove solvents, yielding 1350.7g of a yellow oily 2-([2-(9-anthracene)ethyl]thio)ethanol intermediate.

[0049] 1350 g of the prepared 2-([2-(9-anthrayl)ethyl]thio)ethanol was stirred and added to a reaction vessel containing 2600 g of dichloromethane. Under N2 protection, 18.5 g of 2,6-di-tert-butyl-p-cresol and 900 g of triethylamine were added with stirring. After complete dissolution, 950 g of methacryloyl chloride was added dropwise over 60 min. The temperature was maintained at 2℃, and after the addition was complete, the mixture was allowed to rise to room temperature for 2 h. The organic phase was washed with deionized water, saturated sodium bicarbonate solution, and saturated brine, dried over anhydrous sodium sulfate, filtered, and the filtrate was subjected to vacuum distillation to remove the solvent. The crude product was purified by column chromatography (petroleum ether-ethyl acetate volume ratio = 6:1) to obtain 1323.2 g of 2-[(anthrayl-9-ylethyl)thio]ethyl methacrylate. Yield: 78.1%.

[0050] The 2-[(anthracene-9-ylethyl)thio]ethyl methacrylate compound prepared in Example 2 was subjected to FT-IR and 1H NMR nuclear magnetic resonance spectroscopy. The test results were basically the same as those in Example 1.

[0051] Example 3 Preparation of optical lenses containing 2-[(anthracene-9-ylethyl)thio]ethyl methacrylate (Formula A) 20g of 2-[(anthracene-9-ylethyl)thio]ethyl methacrylate prepared in Example 1 was added to a reaction vessel containing 15g of styrene. The mixture was heated to 50°C and stirred for 20min until completely dissolved. The system was then cooled to 45°C, and 70g of epoxy acrylate EM2380 (Changxing Special Materials Co., Ltd.), 60g of trimethylolpropane triacrylate, and 55g of isobornyl acrylate were added. The mixture was kept under N2 protection throughout the process and stirred at 50°C for 30min. Then, 0.8g of azobisisobutyronitrile and 0.3g of UV absorber UV-326 were added and stirred for 45min to obtain the prepolymer. The prepolymer was degassed under vacuum for 30min, filtered under pressure, and cast. The cast mold was placed in a curing oven and cured at 50°C→60°C→70°C→80°C→95°C for 2h each, followed by annealing at 90°C→80°C→65°C for 1h each. The mixture was cooled to room temperature at a rate of ≤5°C / h, and samples were taken after demolding to obtain acrylic optical lenses.

[0052] Example 4 Preparation of optical lenses containing 2-[(anthracene-9-ylethyl)thio]ethyl methacrylate (Formula A) 18g of 2-[(anthracene-9-ylethyl)thio]ethyl methacrylate prepared in Example 1 was added to a reaction vessel containing 35g of isobornyl acrylate. The mixture was heated to 50°C and stirred for 20 minutes until completely dissolved. The entire process was carried out under N2 protection. The system was then cooled to 45°C, and 80g of epoxy acrylate EM2380 (Changxing Special Materials Co., Ltd.), 40g of trimethylolpropane triacrylate, and 35g of dipropylene glycol diacrylate were added. Then, 0.6g of benzoyl peroxide and 0.3g of UV absorber UV-326 were added and stirred for 40 minutes to obtain a prepolymer. The prepolymer was degassed under vacuum for 30 minutes, filtered under pressure, and cast. The cast mold was placed in a curing oven and cured at 50°C, 60°C, 70°C, and 85°C for 2 hours each, followed by annealing at 80°C and 65°C for 1 hour each. The mixture was then cooled to room temperature at a rate of ≤5°C / h. The acrylic optical lens was obtained by demolding and sampling.

[0053] Example 5 Preparation of optical lenses containing 2-[(anthracene-9-ylethyl)thio]ethyl methacrylate (Formula A) 20g of 2-[(anthracene-9-ylethyl)thio]ethyl methacrylate prepared in Example 2 was added to a reaction vessel containing 20g of styrene. The mixture was heated to 50°C and stirred for 20min until completely dissolved. The system was then cooled to 45°C, and 70g of epoxy acrylate EM2380 (Changxing Special Materials Co., Ltd.), 60g of trimethylolpropane triacrylate, and 55g of isobornyl acrylate were added while stirring. The mixture was kept under N2 protection throughout the process and stirred at 50°C for 30min. Then, 0.8g of azobisisobutyronitrile and 0.3g of UV absorber UV-326 were added and stirred for 45min to obtain the prepolymer. The prepolymer was degassed under vacuum for 30min, pressurized, filtered, and cast. The cast mold was placed in a curing oven and cured at 50°C → 60°C → 70°C → 80°C → 95°C for 2h each, followed by annealing at 90°C → 80°C → 65°C for 1h each. The mixture was cooled to room temperature at a rate of ≤5°C / h, and the acrylic optical lens was obtained by demolding and sampling.

[0054] Example 6 Preparation of optical lenses containing 2-[(anthracene-9-ylethyl)thio]ethyl methacrylate (Formula A) 17g of 2-[(anthracene-9-ylethyl)thio]ethyl methacrylate prepared in Example 2 was added to a reaction vessel containing 35g of isobornyl acrylate. The mixture was heated to 50°C and stirred for 20 minutes until completely dissolved. The entire process was carried out under N2 protection. The system was then cooled to 45°C, and 90g of epoxy acrylate EM2380 (Changxing Special Materials Co., Ltd.), 35g of trimethylolpropane triacrylate, and 30g of dipropylene glycol diacrylate were added. Then, 0.6g of benzoyl peroxide and 0.3g of UV absorber UV-326 were added and stirred for 40 minutes to obtain a prepolymer. The prepolymer was degassed under vacuum for 30 minutes, filtered under pressure, and cast. The cast mold was placed in a curing oven and cured at 50°C, 60°C, 70°C, and 85°C for 2 hours each, followed by annealing at 80°C and 65°C for 1 hour each. The mixture was then cooled to room temperature at a rate of ≤5°C / h. The acrylic optical lens was obtained by demolding and sampling.

[0055] Example 7 Preparation of optical lenses containing 2-[(anthracene-9-ylethyl)thio]ethyl methacrylate (Formula A) 20g of 2-[(anthracene-9-ylethyl)thio]ethyl methacrylate prepared in Example 1 was added to a reaction vessel containing 35g of isobornyl acrylate. The mixture was heated to 50°C and stirred for 20min until completely dissolved. The entire process was carried out under N2 protection. The system was then cooled to 45°C, and 85g of epoxy acrylate EM2380 (Changxing Special Materials Co., Ltd.), 35g of trimethylolpropane triacrylate, and 35g of dipropylene glycol diacrylate were added. Then, 0.6g of benzoyl peroxide, 0.3g of UV absorber UV-326, and 0.2g of octaethylporphyrin nickel were added. The mixture was stirred for 40min to obtain a prepolymer. The prepolymer was degassed under vacuum for 30min, pressurized, filtered, and cast. The cast mold was placed in a curing oven and cured at 50°C, 60°C, 70°C, and 85°C for 2h each. It was then annealed at 80°C and 65°C for 1h each. The mixture was cooled to room temperature at a rate of ≤5°C / h. The mold was then demolded and a sample was taken to obtain an acrylic optical lens.

[0056] Example 8 Preparation of optical lenses containing 2-[(anthracene-9-ylethyl)thio]ethyl methacrylate (Formula A) 15g of 2-[(anthracite-9-ylethyl)thio]ethyl methacrylate prepared in Example 1 was added to a reaction vessel containing 75g of isobornyl acrylate. Under N2 protection throughout, the mixture was heated to 50°C and stirred for 20min. The temperature was then lowered to 45°C, and 55g of epoxy acrylate EM2380 (Changxing Special Materials Co., Ltd.) and 40g of trimethylolpropane triacrylate were added. The mixture was stirred at 50°C for 30min. Then, 0.8g of azobisisobutyronitrile, 0.3g of UV absorber UV-326, and 1.2g of photoinitiator (0.6g TPO + 0.4g 907 + 0.2g ITX) were added, and the mixture was stirred for 45min to obtain the prepolymer. The prepolymer was degassed under vacuum for 30min, pressurized, filtered, and cast. The cast mold was placed in a curing oven, and LED-UV 365nm, 130mW / cm² was turned on. 2 After continuous irradiation for 25 minutes, the temperature was increased to 50℃→60℃→70℃→80℃→95℃ and cured for 1.5 hours each time. Then, the temperature was annealed to 90℃→80℃→65℃ for 1 hour each time. The mixture was cooled to room temperature at a rate of ≤5℃ / h, and the acrylic optical lens was obtained by demolding and sampling.

[0057] Example 9 Preparation of optical lenses containing 2-[(anthracene-9-ylethyl)thio]ethyl methacrylate (Formula A) 18g of 2-[(anthracite-9-ylethyl)thio]ethyl methacrylate prepared in Example 2 was added to a reaction vessel containing 45g of isobornyl acrylate. The mixture was heated to 50°C and stirred for 20 minutes until completely dissolved. The entire process was carried out under N2 protection. The system was then cooled to 45°C, and 70g of epoxy acrylate EM2380 (Changxing Special Materials Co., Ltd.), 35g of trimethylolpropane triacrylate, and 30g of dipropylene glycol diacrylate were added. Then, 0.8g of azobisisobutyronitrile, 0.3g of UV absorber UV-326, and 1.5g of photoinitiator (0.8g TPO + 0.5g 907 + 0.2g ITX) were added and stirred for 40 minutes to obtain the prepolymer. The prepolymer was degassed under vacuum for 30 minutes, pressurized, filtered, and cast. The cast mold was placed in a curing oven, and LED-UV 365nm, 130mW / cm² was turned on. 2 After continuous irradiation for 25 minutes, the temperature was increased to 50℃→60℃→70℃→80℃→95℃ and cured for 1.5 hours each. Then, the temperature was annealed to 90℃→80℃→65℃ for 1 hour each. The acrylic optical lens was then cooled to room temperature at a rate of ≤5℃ / h, demolded, and sampled.

[0058] Comparative Example 1: Preparation of optical lenses without compound A The same method and conditions as in Example 4 were used, except that 18g of 9-anthracene methyl methacrylate was used instead of 2-[(anthracene-9-ylethyl)thio]ethyl methacrylate.

[0059] Comparative Example 2: Preparation of optical lenses without compound A The same method and conditions as in Example 9 were used, except that 18g of 9-anthracene methyl methacrylate was used instead of 2-[(anthracene-9-ylethyl)thio]ethyl methacrylate.

[0060] Example 10: Optical performance testing experiment on the product. The optical properties of the optical materials prepared in Examples 1-9 and Comparative Examples 1-2 were tested. Transmittance was measured using a Lambda 650 S UV-Vis spectrophotometer (PerkinElmer Chemical Analysis Instruments, Inc.), and refractive index was measured using an Rx-7000 digital refractometer (Shanghai Optical Instrument Equipment Co., Ltd.). The testing method involved directly placing the prepared sample (with prepolymer coating) onto the prism of the UV-Vis spectrophotometer or the refractometer for testing. The results are shown in Table 1.

[0061] Table 1 Optical properties of the prepared samples

[0062] Example 11: Optical Imaging Quality Detection Experiment The optical imaging quality of the resin lenses prepared in Examples 4 and 9, and Comparative Examples 1 and 2 was tested. An imported Master2000 high-precision MTF comprehensive image quality analyzer was used. The testing steps were as follows: The lens was placed in a triaxial precision centering fixture. By fine-tuning the X / Y translation and rotation angles, and coordinating with real-time light spot acquisition by the equipment, the geometric center and optical center of the lens were ensured to be completely aligned with the main optical axis of the equipment. A CCD was used to acquire fringe images at spatial frequencies of 10~100 lp / mm. White light MTF curves were generated by software. By identifying the coordinates of all grid intersections and comparing them with the coordinates of the ideal distortion-free grid, the full field-of-view distortion rate was automatically calculated. MTF curves for each field of view under three colors (R / G / B) were acquired, and the offset of the three monochromatic curves was compared by software. The test results are shown in Table 2.

[0063] The test results show that the distortion rate of the example lens across the entire field of view is ≤0.52%, and the overlap of the three-color MTF is highly consistent; the distortion rate of the comparative lens across the entire field of view is ≤1.17%, and the axial and transverse curves of the three-color MTF deviate to some extent. These results indicate that the example lens exhibits no significant distortion and excellent dispersion control in actual imaging.

[0064] Table 2 Comparison of Image Quality of Samples (Lens)

[0065] Example 12: Mechanical property testing experiment Static pressure resistance test method: Select a substrate with a certain curvature at the center thickness, fix it convex side up on a steel structure support. The steel structure support has a cylindrical groove. Place a piece of white paper at the bottom of the groove, and cover it with carbon paper. Apply a load of 105N at a speed of 9mm / min, hold the pressure for 10 seconds, and observe whether any marks appear on the white paper or cracks appear on the sample. This test is based on the national mandatory standard GB 45184-2024 "Safety Technical Specifications for Components in Optometry Products". The test results are shown in Table 3.

[0066] The static pressure resistance test results showed that samples from Comparative Example 1 and Comparative Example 4 both had cracks; while samples from Example 4 and Example 9 showed no marks on the white paper. This indicates that the samples from the Examples have superior static pressure resistance.

[0067] Table 3. Experimental data on mechanical properties

Claims

1. An anthracene heterocyclic thioacrylate compound, characterized in that, Its structure is shown in equation (A): (A)。 2. The method for preparing the compound according to claim 1, characterized in that, The method includes the following steps: I. Thioetherification reaction: Dissolve 9-anthracene ethyl mercaptan in an anhydrous solvent, cool to -3~0℃ in an ice bath, and purge with N2 throughout the process; add acid-base solution dropwise and stir for 10~20 min, then add 2-chloroethanol dropwise for 90~120 min, and raise the temperature to room temperature for 3~6 h. The molar ratio of 9-anthracene ethyl mercaptan, acid-base solution and 2-chloroethanol is 1:(1.2~2.5):(1.5~3.5); filter to remove salt, and rotary evaporate to remove solvent, to obtain a yellow oily 2-([2-(9-anthracene)ethyl]thio)ethanol intermediate; II. Esterification reaction: Add polymerization inhibitor, 2-([2-(9-anthrayl)ethyl]thioethanol and acid-base solution to a reaction vessel containing solvent. Probe with N2 throughout the reaction. Cool to -3~0℃ in an ice bath. Stir until completely dissolved. Slowly add methacryloyl chloride, controlling the temperature <5℃. After addition, raise the temperature to room temperature and react for 1.5~2.5h. The molar ratio of 2-([2-(9-anthrayl)ethyl]thioethanol, acid-base solution, and methacryloyl chloride is 1:(1.2~3):(1.5~3.5). After the reaction, raise the temperature to room temperature. Wash the organic phase with deionized water, saturated sodium bicarbonate solution, and saturated brine until neutral. Dry with anhydrous sodium sulfate, filter, and remove the solvent from the filtrate by vacuum distillation. The crude product is purified by column chromatography with a petroleum ether-ethyl acetate volume ratio of (7~3):1, yielding compound (A) 2-[(anthrayl-9-ylethyl)thio]ethyl methacrylate.

3. The preparation method according to claim 2, characterized in that, The solvent in step I is selected from at least one of diethyl ether, tetrahydrofuran, dichloromethane, cyclopentyl methyl ether, dimethyl sulfoxide, and isopropyl acetate; the molar ratio of 9-anthraethylthiol to the solvent is 1:(3~9).

4. The preparation method according to claim 2, characterized in that, The solvent in step II is selected from at least one of dimethyl sulfoxide, N,N-dimethylacetamide and N,N-dimethylformamide; the molar ratio of 2-([2-(9-anthrayl)ethyl]thio)ethanol to the solvent is 1:(3~9).

5. The preparation method according to claim 2, characterized in that, The acid-base solution used in steps I and II is selected from at least one of dimethylamine, diethylamine, triethylamine, potassium carbonate, sodium carbonate, sodium hydroxide, potassium hydroxide, and 4-dimethylaminopyridine.

6. The preparation method according to claim 2, characterized in that, In step II, the polymerization inhibitor is at least one of hydroquinone, hydroquinone monomethyl ether, and 2,6-di-tert-butyl-p-cresol.

7. The preparation method according to claim 2 or 6, characterized in that, The molar amount of the polymerization inhibitor is 1 to 3% of the molar amount of 2-([2-(9-anthrayl)ethyl]thioethanol).

8. The application of the anthracene heterocyclic thioacrylate compound as described in claim 1 in the preparation of modified acrylic optical resin optical materials.

9. A modified acrylic optical resin optical material, characterized in that, The material is polymerized from the anthracene heterocyclic thioacrylate compound of claim 1 and acrylate monomers.

10. The modified acrylic optical resin optical material as described in claim 9, characterized in that, The acrylate monomers include at least one of epoxy acrylate, trimethylolpropane triacrylate, isobornyl acrylate, and dipropylene glycol diacrylate.

Citation Information

Patent Citations

  • Raw material composition for preparing acrylic optical coating and raw material composition for preparing acrylic optical lens

    CN122080715A

  • Sulfur-containing aromatic acrylate compound as well as preparation method and application thereof

    CN122355888A